Technology and Media in Education - Hrvoje Budić; Antun Marinac; Filip Filipović (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
The aim of this paper is showing the importance of using modern communication technologies, as well as the media in educational development. The introductory will show importance of technological changes in educational development with special emphasis on the development of online learning and its basic features. Here, the importance of informational infrastructure development will also be shown, as a critical element for Internet learning development. Furthermore, different media used in education, related to their characteristics, will also be analyzed. The paper will use descriptive method, method of analysis, induction and deduction. Conclusion will show current trends and technologies, as well as a critical overview of entire paper. Results will be used as a reference frame for future continuous research.
Keywords: A20; 330; ICT (Information and Communication Technology); E – learning; multimedia; Web 2. 0 tools; M – learning